THEOLOGICAL APPROACH TO ENVIRONMENTAL ISSUE - Lunić, Tomislav; Ćesarević, Jelena (Napredak, 2020)
The environmental issue is a multidimensional problem caused by the detrimental impact that human activity is having on the environment. In the first part of the study, we highlight several consequences of accelerated industrial development, technological growth and development: pollution of water; shortage of natural resources due to uncontrolled exploitation; degradation of biodiversity; climate change, etc. Additionally, in the study we focus is on man who, on the one hand, raises ecological awareness, by establishing different programs, organizations and various action plans, while on the other, through raw exploitation and spending natural resources, contributes to the ongoing imbalance in the ecosystem, and in essence, God’s creation as a whole. The blame lies with man, and not nature. The destruction starts with the Biblical Fall and continues to this very day. In this regard, there are different solutions for switching to healthy technologies, green economy. Thus, the theological solution is based on establishing harmony between the God, man and environment, which in the liturgical sense of the cosmos can stop the destruction of the environment, i.e., environment as a whole. Therefore, the environment is entrusted to man as God’s gift to save and cherish it a Eucharistic, liturgical, priestly manner.